Congenital Lipoid Adrenal Hyperplasia, as a Poorly Understood Cause of 46 XY Sexual Differentiation Disorder - Raúl Villanueva Rodríguez; Alberto Vielma Valdez; Maricruz Cassou Martinez; Laura Leticia Pérez Corrales; Ramón G. de los Santos Aguilar; Luis David Sol Oliva (Case Reports in Endocrinology)
Summary. Disorders of sexual differentiation are defined as congenital alterations between chromosomal, gonadal, and phenotypic sex. The principal cause of these disorders is an adrenal origin; however, there are infrequent causes, such as congenital lipoid adrenal hyperplasia. Case. We present the case of a woman who, during the neonatal period, presented salt-losing adrenal insufficiency associated with 46 XY gonadal dysgenesis. The genetic study found a steroidogenic acute regulatory protein (StAR) mutation. Conclusion. Mutations in StAR result in a nonfunctional protein, which clinically translates into congenital adrenal hyperplasia and, in the case of patients with 46 XY karyotype, is accompanied by gonadal dysgenesis characterized by androgen deficiency, without alterations in anti-Müllerian hormone.